Penyuluhan Penggunaan Dan Penyimpanan Vitamin C Kepada Pkk Rw 02 Dan 09 Kecamatan Panyileukan Bandung - Ani Anggriani; Ade Tika H; Siti Saidah; Winasih Rachmawati; Ida Lisni; Amida Sriwianti (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Vitamin C has a very important role related to various processes that occur in the body, especially during the Covid-19 pandemic that has hit all countries in the world for 2 years, this vitamin is much sought after. Vitamin C plays a role in maintaining and making the body's immune system work more optimally, helping the process of forming protein, collagen, and helping to increase iron absorption in the body. The occurrence of panic buying in the community with the stockpiling of vitamin C products which has an impact on the high price of the vitamin, so that the vitamin is in short supply. In fact, you can get vitamin C by consuming foods that contain vitamin C. With the rampant accumulation of vitamin C with storage for too long it will affect the levels of vitamin C itself, and excessive consumption of vitamin C will have a bad impact on the body. For this reason, so that people understand the importance of using Vitamin C correctly and how to store Vitamin C, community service is carried out which will be provided through counseling to PKK cadres RW 02 and RW 09 Panyileukan Bandung. The method used is to conduct an offline webinar to related PKK cadres on the use and storage of vitamin C with speakers from the lecturers of the pharmacy faculty.